Effect of the Degenerative State of the Intervertebral Disk on the Impact Characteristics of Human Spine Segments - Wilson, Sara; Alkalay, Ron N.; Myers, Betsy R. (Frontiers in Bioengineering and Biotechnology, 2013)
Models of the dynamic response of the lumbar spine have been used to examine vertebral fractures during falls and whole body vibration transmission in the occupational setting. Although understanding the viscoelastic stiffness or damping characteristics of the lumbar spine are necessary for modeling the dynamics of the spine, little is known about the effect of intervertebral disc degeneration on these characteristics at high loading rates. We hypothesize that disc degeneration significantly affects the viscoelastic response of spinal segments to high loading rate. We additionally hypothesize the lumbar spine stiffness and damping characteristics are a function of the degree of preload. A custom, pendulum impact tester was used to impact 19 L1-L3 human spine segments with an end mass of 20.9kg under increasing preloads with the resulting force response measured. A Kelvin–Voigt model, fitted to the frequency and decay response of the post-impact oscillations was used to compute stiffness and damping constants. The spine segments exhibited a second-order, underdamped response with stiffness and damping values of 17.9 - 754.5kN/m and 133.6 - 905.3Ns/m respectively. Regression models demonstrated that stiffness, but not damping, significantly correlated with preload (p